INFLUENCE OF PERCEPTION IN THE GENERATION AND MANAGEMENT OF GROUP CONFLICT: AN EXAMINATION OF HETEROGENEOUS SOCIETY (LAPAI JOURNAL OF NIGERIA HISTORY, 2024)
This paper examines the influence of perception in the generation and management of group conflict within a heterogeneous society, with a specific focus on Nigeria. The study employs a qualitative methodology, drawing on secondary data from existing literature, historical accounts, and policy documents to analyse the causes of social conflicts in Nigeria, which are traced back to colonial legacies. The philosophy behind the introduction of education in Nigeria is critically reviewed, highlighting its intended role in enhancing self-reliance, fostering national unity, and promoting social cohesion. The paper explores the limitations of education in achieving these objectives and identifies gaps in its implementation as a tool for proactive conflict management. Based on the findings, the paper proffers recommendations for adopting a re-engineered approach to education that emphasizes peace building, civic responsibility, and national integration. The study concludes that while education was originally designed to mitigate social conflicts, its impact has been limited, necessitating urgent reforms to ensure it effectively supports Nigeria’s development goals.